1994
DOI: 10.1523/jneurosci.14-07-04025.1994
|View full text |Cite
|
Sign up to set email alerts
|

Vocal-acoustic pathways in a teleost fish

Abstract: Many teleost fish generate acoustic signals for vocal communication by the synchronized, high-frequency contraction of skeletal, sonic muscles. In midshipman, eight groups of brainstem neurons were distinguished after biocytin application to the sonic nerve that, we propose, represent the entire vocal motor circuit. Biocytin-filled terminals were ubiquitous within all areas containing labeled neurons and, together with ultrastructural evidence, suggested a serial, transneuronal transport at synaptic sites betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
268
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(290 citation statements)
references
References 28 publications
21
268
0
Order By: Relevance
“…Multiple lineages of teleost fish have independently evolved sonic communication systems by using a diversity of mechanisms, including the vibration of the swimbladder by specialized muscles at frequencies of hundreds of hertz (39)(40)(41)(42). It would be intriguing to determine whether a comparable convergent compartmentalization and specialization of Na ϩ channels genes occurs in muscles specialized for acoustic communication to allow for rapid or prolonged firing of muscle fibers needed to generate acoustic signals.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lineages of teleost fish have independently evolved sonic communication systems by using a diversity of mechanisms, including the vibration of the swimbladder by specialized muscles at frequencies of hundreds of hertz (39)(40)(41)(42). It would be intriguing to determine whether a comparable convergent compartmentalization and specialization of Na ϩ channels genes occurs in muscles specialized for acoustic communication to allow for rapid or prolonged firing of muscle fibers needed to generate acoustic signals.…”
Section: Discussionmentioning
confidence: 99%
“…VS measures from 0 to 1 the accuracy of phase locking to a periodic signal (Goldberg and Brown, 1969). In addition, vector strength of synchronization to the beat frequency, VS dF , was measured by construct- Bass et al, 1994). B, Line drawing of cross-section at level of midbrain recording site.…”
Section: Methodsmentioning
confidence: 99%
“…Anatomical studies have shown a connection between the vocal motor system and an efferent nucleus in the rostral medulla that innervates inner ear end organs and mechanosensory lateral line receptor organs (Bass et al, 1994). Given the encoding of vocal parameters by both the auditory (for review, see Bass and McKibben, 2003) and lateral line systems in midshipman fish, we hypothesized that the efferent system is activated during sound production, leading to changes in the neuronal activity of both inner ear and lateral line primary afferents.…”
Section: Introductionmentioning
confidence: 99%